Foreword - Horton, Tammy; Błażewicz-Paszkowycz, Magdalena; Staples, David A.; Bird, Graham J. (Zootaxa, 2015)
This special issue honours the life and work of Roger Bamber, who made an outstanding contribution to the field of marine biology and taxonomy.  Roger died in February 2015 at the age of 65, from complications arising from severe motor neuron disease (Amyotrophic lateral sclerosis). This was a tragic loss for his former wife Jane, family and all who knew him.      The editors chose Zootaxa for this special issue since Roger had considerable involvement with the journal over many years as subject editor for the Pycnogonida, Tanaidacea and Cumacea. We are grateful to Zhi-Qiang Zhang, Editor-in-Chief of Zootaxa, for making this possible.